MANAGED AQUIFER RECHARGE FEASIBILITY USING WEIGHT FACTOR INDEX METHOD IN SUPHANBURI, THAILAND - Tanachaichoksirikun, Pinit; Xiao, Xi; Sirikaew, Uba; Seeboonruang, Uma (My University, 2025)
Managed Aquifer Recharge (MAR) is a technique used to intentionally enhance groundwater recharge by directing surface water or treated wastewater into underground aquifers. MAR offers several advantages for sustainable water resources management and ecosystems, namely, groundwater replenishment, drought resilience, and flood protection. Suphanburi Thailand faced challenges related to both floods and droughts because of variable rainfall patterns and hydrological conditions. Then, MAR is a good challenge for flood control and drought protection. This research aims to develop the model and find the optimal location and recharge type for set-managed aquifer recharge in Suphanburi, Thailand. Data, such as climate, land used, hydrology, and hydrogeology were carried out and provided the optional location to construct MAR. The model was developed using the Weight Factor Index Method. The results revealed that the suitable location for MAR was in the Tha Chin River area, due to the high rainfall, which allows for the storage of large quantities of water during the rainy season in the MAR in the event of groundwater shortages. Proper recharge of the river can dilute contaminants in groundwater and improve groundwater quality. The findings provided valuable guidelines for planners, decision-makers, and hydrogeologists in designing future artificial recharge projects within a similar area, ensuring a reliable water supply and the sustainable use of groundwater over the long term. In conclusion, the integration of WFI and GIS is recognized as an effective method for limited data, and location, and reducing errors.
Keywords: Flood and Drought Solving; Managed Aquifer Recharge Feasibility; Optimal Location; Weight Factor Index Method